The Influence of Rice Production, Rice Prices, Exchange Value on Rice Imports Islamic Perspective Review - Natari Manik Manik, Febriyani; Harahap, Isnaini; Ahmadi Bi Rahmani, Noor (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Indonesia is an agricultural country where the source of livelihood for most of its population is in the agricultural sector. Indonesia is called an agricultural country because it has abundant natural resources and extensive agricultural land. However, just having a large area of ??land and getting the title of an agricultural country does not mean that you can produce your own food. The large population is one of the factors that influences Indonesia to import food commodities to meet basic domestic needs. This research aims to determine the influence of rice production, rice prices, exchange rates on rice imports from an Islamic perspective. The research method uses a quantitative approach with the VAR/VECM method. The data collected is secondary data and analyzed using software Eviews 13. The sample for this research is monthly and annual data on rice production, rice prices, exchange rates and rice imports from 2000-2023. The research results show that rice production partially influences rice imports. Rice prices influence rice imports. The exchange rate partially has a significant negative effect on rice imports and rice production, rice prices, the exchange rate partially has a significant negative effect on rice imports.